New species of Dyckia (Bromeliaceae) from Brazil - Leme, Elton M.c.; de C. Ribeiro, Otávio B.; Miranda, Zenilton De J. G. (Phytotaxa, 2012)
We describe and illustrate 10 new Dyckia species from the Brazilian states of Goiás, Mato Grosso, Mato Grosso do Sul, Minas Gerais and Paraná: Dyckia acutiflora, D. areniticola, D. formosensis, D. glabrifolia, D. gouveiana, D montezumensis, D. pottiorum, D. rondonopolitana, D. secundifolia and D. walteriana. The morphological affinities of the new taxa are also discussed.